Impact of oral hygiene instructions on cytokines in smokers and vapers with gingivitis - Albuslutan, Abdulrahman A; Saliem, Saif S; Shibli, Jamil (Journal of Baghdad College of Dentistry, 2025)
Background: Cigarette smoking (CS) is a periodontal disease risk factor, affecting clinical parameters such as bleeding on probing (BOP), plaque index (PI), gingival index (GI) and proinflammatory cytokines level. This study examines the impact electronic cigarette use on proinflammatory cytokines and periodontal parameters. Methods: In this non-randomized study, ninety participants diagnosed with gingivitis were assigned into three groups. examined the effect of oral hygiene instructions on periodontal parameters and inflammatory biomarkers. Thirty CS (n=30) vaping electronic-cigarettes (e-cig) (n=29), and non-smoker (NS) (n=31) was included. Clinical parameters including PI, BOP, and GI were recorded at baseline and after 3 weeks. Enzyme-linked immunosorbent assay was used to assess levels of matrix metalloproteinases (MMP)-8 and matrix metalloproteinases (MMP)-9 in saliva at baseline and after 3 weeks. Results: CS and vapers exhibited significantly higher PI, GI, MMP-8 and MMP-9 scores compared to NS before and after the oral hygiene instructions, indicating greater periodontal inflammation. CS as well as individuals who use electronic cigarettes exhibited reduced BOP, likely because nicotine-induced vasoconstriction conceals the actual severity of inflammatory periodontal disease. Conclusion: CS and electronic cigarette use adversely affect periodontal health, increasing PI, GI, MMP-8 and MMP-9 levels while altering BOP. These findings stress the importance of tailored maintenance of periodontium smokers and vapers through integrating vaping cessation into treatment protocols to improve oral health outcomes.